(untitled) (Hekima Review, 1994)
Asked why he decided not to be baptized after his catechetical instructions, an old man at the time of the early missionary activities in Africa replied, "I'll be alone· in heaven when I go there, because my grandfathers, mothers and the rest of my family who died as pagans, will not be present". Certainly, this teaching belongs to the old missionary theology which we would find difficult to defend today. Remarkable about the response of the old sage, however, is his deep insight into the mystery of life after death. If heaven is communion, then ·it should not only be with God but also with all our dear ones, 'pagans' inclusive. Grace for the old man is not only God's self-giving that saves souls but also more importantly God's self-giving that builds communion and fosters communion even after death.